Coordinated Power Scheme to Mitigate Power Curtailment in the Application of a Microgrid - Heesang Ko; Gihoon Kim; Yanghyun Nam; Kyungsang Ryu (Research Developments in Science and Technology Vol. 8, 2022)
There have been instances where the output of renewable energy (RE) has been reduced as the share of RE has increased. In the current energy market, as the share of photovoltaics (PV) grows, wind power (WP) curtailments grow as well, compounding the difficulties faced by wind farm operators. A supervisory power coordination technique is proposed in this study. The major goals are to avoid extra power from REs from entering the grid, which would result in curtailments. In order to make it feasible, the proposed scheme is to design a grid-connected microgrid system to be operated only in response to loads and virtual power plant (VPP) requests such that the system is operated as an independent microgrid when there is no VPP request. Simulation simulations in the MATLAB/Simulink environment were used to verify the effectiveness of the suggested method. The verification was conducted based on the voltage criteria, such as the AC voltage regulation between ±6% of the rated AC voltage, the DC voltage regulation between ±10% of the rated DC voltage, the power balance according to variations in the loads, and VPP requests for power. The simulation revealed that the proposed strategy is both possible and justified, not only for mitigating power curtailment but also for implementing various system configurations.